Early Experience of Minimally Invasive Tubular Lumbar Microdiscectomy at a Tertiary Care Centre in Nepal - Pradhanang, Amit; Sedain, Gopal; Karki, Anjan Singh; Bohara, Sandeep; Shrestha, Dipendra Kumar; Sharma, Mohan Raj; Shilpakar, Sushil Krishna; Jha, Prabhat (Journal of Institute of Medicine Nepal, 2024)
IntroductionLumbar disc herniation is a leading cause of low back pain and radiculopathy. Open microdiscectomy, though effective, involves muscle dissection and longer recovery. Minimally invasive tubular microdiscectomy aims to reduce these drawbacks. This study evaluates its early outcomes in Nepal.MethodsOur observational study included patients who underwent MIS tubular lumbar microdiscectomy at our hospital from August 2023 to July 2024. Data on operative duration, blood loss, and return to work time were collected. Functional outcomes were assessed at three months using the Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for spinal and radicular pain.ResultsA total of 22 patients were included. The mean operative duration was 121.5 ± 31.67 minutes, and mean intraoperative blood loss was 60 ± 20.17 mL. The mean return to work time was 1.86 ± 0.2 weeks. At three months, the mean ODI score significantly improved from 54.36 ± 8.8 to 0.91 ± 1.47 (p < 0.001). VAS scores for spinal pain decreased from 3.05 ± 0.84 to 1.5 ± 0.3 (p < 0.001), and radicular pain from 4.91 ± 0.86 to 1.36 ± 0.65 (p < 0.001). No major complications occurred, and 5% of patients had transient paresthesia, which resolved spontaneously.ConclusionMIS tubular lumbar microdiscectomy is an alternative procedure for lumbar disc herniation, offering short-term functional improvement. Long-term comparative studies are needed to assess its durability against open microdiscectomy.